Distinct clinical and laboratory characteristics of latent autoimmune diabetes in adults in relation to type 1 and type 2 diabetes mellitus - Pipi, Elena (Baishideng Publishing Group Inc, 2014)
Ever since its first appearance among the multiple forms of diabetes, latent autoimmune diabetes in adults (LADA), has been the focus of endless discussions concerning mainly its existence as a special type of diabetes. In this mini-review, through browsing important peer-reviewed publications, (original articles and reviews), we will attempt to refresh our knowledge regarding LADA hoping to enhance our understanding of this controversial diabetes entity. A unique combination of immunological, clinical and metabolic characteristics has been identified in this group of patients, namely persistent islet cell antibodies, high frequency of thyroid and gastric autoimmunity, DR3 and DR4 human leukocyte antigen haplotypes, progressive loss of beta cells, adult disease onset, normal weight, defective glycaemic control, and without tendency to ketoacidosis. Although anthropomorphic measurements are useful as a first line screening, the detection of C-peptide levels and the presence of glutamic acid decarboxylase (GAD) autoantibodies is undoubtedly the sine qua non condition for a confirmatory LADA diagnosis. In point of fact, GAD autoantibodies are far from being solely a biomarker and the specific role of these autoantibodies in disease pathogenesis is still to be thoroughly studied. Nevertheless, the lack of diagnostic criteria and guidelines still puzzle the physicians, who struggle between early diagnosis and correct timing for insulin treatment.